KETIK MANAJEMEN PENANGKARAN KUPU-KUPU SAYAP BURUNG (Ornithoptera priamus) DI SUAKA MARGASATWA SIDEY WIBAIN - Resti I Widiastuti; Keliopas Krey; Ursula P Maker (VOGELKOP: Jurnal Biologi, 2023)
The Bird Wing Butterfly (Ornithoptera priamus) is the spesies of butterfly that is most in demand by collectors because of the beauty of its wings and is included in the CITES Appendix II list. This study to analyze the management flow of captive bird wings (Ornithoptera priamus) in Sidey Wibain Wildlife Reserve, identify biotic and abiotic conditions of captive land and analyze the value of direct benefits of butterflies for communities around the Sidey Wibain Wildlife Reserve. The method used in this research is descriptive method, with direct observation (observation) in the field, and also carrying out FGD (Focus Group Discussion) activities. The procedure used in this study is preparation of site selection, land preparation for breeding. The data obtained is tabulated and described. The results showed that the management of butterfly breeding in Sidey Wildlife Reserve was participatory with the involvement of MAPALA, UNIPA, CI, BKSDA, PT Rizky Perdana and the Biology Department of UNIPA. The management flow of the butterfly breeding includes three main stages, namely the development of captivity, feed maintenance and cocoon marketing. The value of the benefits of butterflies obtained by the community is the direct benefit value, because the cocoon harvest will be sold.